Optimalisasi Nilai Perusahaan Melalui Struktur Modal, Perencanaan Pajak, dan Pertumbuhan Penjualan: Peran Kinerja Keuangan sebagai Variabel Moderasi - Ningsih, Fitria Eka; Stiawan, Hari; Nurhayati, Nurhayati (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
This research aims to determine the influence of capital structure, tax planning and sales growth on company value with financial performance as a moderating variable in LQ45 index companies. This type of research is quantitative using secondary data obtained from the Indonesian Stock Exchange (BEI) and the website of each company and the analysis technique used in this research uses multiple linear regression and Moderated Regression Analysis (MRA) with the help of the E-views version of the software. 9. Research was conducted on LQ45 index companies. The data sampling technique used purposive sampling, the research samples were 13 companies with observations for 5 years 2018-2022. The results of this research show that partially, capital structure has a negative effect on company value. Partially, tax planning has no effect on company value. Partially, Sales Growth has no effect on Company Value, Simultaneously the variables capital structure, tax planning and sales growth influence company value, company performance as a moderating variable influences company value, and in model 2 the interaction of capital structure and company performance influences company value.